Fatigue design and prevention in movable scaffolding systems = Projektowanie ruchomych systemów rusztowań z uwzględnieniem obciążęń zmęczeniowych - Coelho, Hugo; Torres, Alberto; Pacheco, Pedro; Moreira, Cristiano; Silva, Rute; Soares, José M.; Pinto, Dânia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Movable Scaffolding System (MSS) is a heavy construction equipment used for casting situ of concrete bridge decks. In the past decades, MSSs have become increasingly complex and industrialized, enlarging its span ranges, incorporating auxiliary elevation machinery and increasing productivity. The tendency nowadays is for strong reutilization and the notion of MSS as a disposable or temporary structure is somehow reductive.
Keywords: bridge construction; MSS; Movable Scaffolding System; fatigue; mosty; system ruchomych rusztowań; obciążenia zmęczeniowe